Information sharing : Beneﬁts - Mendes Calo, Karla (2012)
Government Information Sharing (GIS) allows information exchange and integration between different government departments, agencies, as well as between public and private institutions. Sharing information enables enhanced efﬁciency -avoiding duplication of processes updating the same data; better quality of processes and services- removing inconsistent data and reducing error; and improved transparency -facilitating access to information. The implementation of GIS initiatives requires technological, organizational, institutional and environmental changes. Therefore, the deﬁnition of compeling business cases is required, while studying the feasibility of such initiatives. In this work, we present ﬁndigs of our research work studying beneﬁts of GIS. Based on secondary data collection and surveyed GIS initiatives implemented in several countries, we present a comprehensive study of beneﬁts in GIS. The main contribution of this paper is to provide a detailed list of feasible GIS beneﬁts and a classiﬁcation of such beneﬁts, providing a rigorous benchmark to justify the implementation of GIS initiatives.